1988
DOI: 10.1002/tera.1420380510
|View full text |Cite
|
Sign up to set email alerts
|

Vitrification of mouse oocytes results in aneuploid zygotes and malformed fetuses

Abstract: Vitrification of mouse oocytes adversely affected the subsequent developmental potential of embryos and fetuses derived from the fertilization of such oocytes after thawing. Only 5% of oocytes vitrified formed viable fetuses on the 15th day of gestation as compared to 47% in the controls. The incidence of chromosomally aneuploid zygotes, derived from cryopreserved oocytes, was approximately threefold higher than the controls irrespective of whether the oocytes were cryopreserved by vitrification or DMSO slow-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
3
2

Year Published

1991
1991
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(50 citation statements)
references
References 20 publications
3
42
3
2
Order By: Relevance
“…Contrary to the complete cryopreservation process (Kola et al, 1988;Carroll et al, 1989;Bouquet et al, 1992; present study), the exposure of oocytes to cooling to 0°C and/or to DMSO does not induce an increased total number of morphological abnormalities. This result, which is in accordance with the observations of Glenister et al (1987), suggests that the important cellular damage after oocyte cryopreservation is due to events taking place at the time of freezing from 0°C to -196°C andlor thawing.…”
Section: Morphological Abnormalitiescontrasting
confidence: 74%
“…Contrary to the complete cryopreservation process (Kola et al, 1988;Carroll et al, 1989;Bouquet et al, 1992; present study), the exposure of oocytes to cooling to 0°C and/or to DMSO does not induce an increased total number of morphological abnormalities. This result, which is in accordance with the observations of Glenister et al (1987), suggests that the important cellular damage after oocyte cryopreservation is due to events taking place at the time of freezing from 0°C to -196°C andlor thawing.…”
Section: Morphological Abnormalitiescontrasting
confidence: 74%
“…In contrast, Kola et al (1988) after analyzing a much smaller sample of mouse embryos at first cleavage detected almost a three fold increase in aneuploidy in embryos derived from frozen-thawed oocytes.…”
Section: Introductionmentioning
confidence: 82%
“…Both DMSO and PROH have higher membrane permeability than glycerol [52][53][54]. However, it has been reported that DMSO causes spindle polymerization in oocytes with increased potential for polyploidy [35,[56][57][58][59]. In addition, it has been known that the toxicity of DMSO for oocytes and embryos is related to the duration and temperature at which exposure occurs, indicating that oocytes in which are exposed to DMSO at lower temperatures have a better outcome [39,[60][61].…”
Section: Discussionmentioning
confidence: 99%